2006
DOI: 10.5694/j.1326-5377.2006.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the mental health of refugees with temporary versus permanent protection visas

Abstract: Objectives: To determine the impact of the Australian provisions for temporary rather than permanent protection for asylum seekers found to be genuine refugees. Design and setting: A comparison of the mental health of Persian‐speaking refugees with temporary (n = 49) versus permanent (n = 67) protection visas attending an early intervention program in Sydney, New South Wales, 2002–03. Measures: Standard measures were used to assess past trauma, detention experiences, postmigration stresses, symptoms of post‐tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(142 citation statements)
references
References 31 publications
6
127
0
1
Order By: Relevance
“…The same study showed that people with post-migratory living difficulties were more likely to have PTSD compared with people without difficulties. Likewise, Swedish and Australian cross-sectional studies showed that individuals with PMLDs were more likely to suffer from MH diagnoses that also included depression and anxiety [2, 36, 37]. Some Dutch studies associated long asylum procedures, lack of work and family issues with significant impacts on anxiety, depressive and somatoform disorders [4, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The same study showed that people with post-migratory living difficulties were more likely to have PTSD compared with people without difficulties. Likewise, Swedish and Australian cross-sectional studies showed that individuals with PMLDs were more likely to suffer from MH diagnoses that also included depression and anxiety [2, 36, 37]. Some Dutch studies associated long asylum procedures, lack of work and family issues with significant impacts on anxiety, depressive and somatoform disorders [4, 38].…”
Section: Discussionmentioning
confidence: 99%
“…exposure to acts of violence, not receiving adequate medical attention etc.) that contributed to PTSD (but not depression) [47]. This suggests that more research may be required to elucidate further the association of length of time in detention and long-term mental illness in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the use of temporary protection appears to be a viable solution only when there is a clear commitment by recipient countries to return evacuees once safety has been fully restored to the source country. The use of temporary protection provisions for populations who remain at risk of persecution, as occurred with refugees arriving through irregular migration channels in Australia [22], appears to be a highly counterproductive approach that leads to adverse mental health outcomes that persist until permanent protection is granted [23],[24].…”
Section: Strategies To Manage Migrationmentioning
confidence: 99%
“…Mental health research indicates that rates of mental disorder amongst populations held in detention are substantially higher than compatriots held in community settings [22],[37][40]. Children in particular show evidence of severe mental health impairment [41][44].…”
Section: Interception and Confinementmentioning
confidence: 99%
See 1 more Smart Citation